The Relationship between Regulation Governing Use of Geographical Indications and Traditional Knowledge: the case of guarana involving the territories of Maués and of Indigenous Land Andirá-Marau - Martins, Igor Schumann Seabra (2020)
The cases "Maués" indication of source and "Andirá-Maraú" appellation of origin application related to guarana were analyzed regarding the strategic role of geographical indication regulation governing use in the preservation of productive practices and traditions of the collectivity. Documentary research involving the administrative processes at INPI of these geographical indications was performed. Regulation governing use showed strategic for the collectivity that uses the geographical indication, since it has a direct relation with product identity and typicity, valuing its main characteristics and the close connection with the geographic origin. In the case of “Maués” indication of source, the Sateré-Mawé Producers Consortium verified that regulation governing use would not be adequate in preserving and valuing the traditional forms of production of its collectivity, mainly the agroforestry methods of guaraná production, which motivated an own application of appellation of origin.